Linguistic Privilege and Justice: What Can We Learn from STEM? - Pronskikh, Vitaly (Philosophical Papers, 2018)
The linguistic privilege of native speakers in scientific communication, both oral and written, has been widely reported to influence researchers’ publications and careers in and beyond academia. I examine social structure and communication in the Science, Technology, Engineering and Mathematics (STEM) fields through the example of big science and attempt to answer the question of why language injustice has a less significant effect on non-native scientists and engineers than on philosophy scholars. I do so by scrutinizing the role of signs and nonlinguistic boundary objects in STEM practice and written communication. I also argue that although high-energy physics is relatively linguistically inclusive, it is marked by linguistic privilege of certain groups that bears a structural character which is not common in STEM and is predominant mainly in megascience. I finally suggest that insofar as rhetoric in STEM is generally modest, its practices can serve as an example for analytic philosophy, which also aims at minimizing rhetoric.